Measuring beliefs about gluten free diet adherence in adult coeliac disease using the theory of planned behaviour - Sainsbury, K.; Mullan, Barbara (Elsevier BV, 2011)
The theory of planned behaviour (TPB) was used to elicit the salient beliefs about gluten free diet (GFD) adherence in adults with coeliac disease (CD) and to design a TPB questionnaire to predict adherence levels. This questionnaire was administered to 265 CD participants with adherence and quality of life (QOL) measures, a GFD knowledge test, and self-reported psychiatric history. Regression analyses were used to test the fit of the TPB in predicting adherence, and to determine the nature of the relationships between adherence, QOL, knowledge, and psychiatric history. The TPB combined with self-reported depression and anxiety, and QOL explained significant variance in intention (41.0%) and adherence (33.7%). Poorer dietary adherence and psychiatric history were also associated with lower QOL. Findings suggest that the TPB provides an adequate model for predicting GFD adherence in CD, and the presence of psychiatric conditions represents a potential intervention target to improve adherence and QOL.